THE INFLUENCE OF FINANCIAL KNWOLEDGE AND DIGITAL PAYMENT ON FINANCIAL MANAGEMENT BEHAVIOR WITH COMSUPTIVE BEHAVIOR AS A MODERATING VARIABLE - Izza, Aqidatul; Mardiana, Mardiana (Universitas Islam Lamongan, 2024)
The purpose of this study is to test and analyze the effect of financial knowledge and digital payment on financial management behavior with consumptive behavior as a moderating variable for students of UIN Maulana Malik Ibrahim Malang. The type of research is associative quantitative. The data used is primary data. In collecting data, this study used the questionnaire distribution method. In this study using 391 respondents. To analyze the data results, researchers used smartPLS 4.0 software tools This study proves that financial knowledge and digital payment have a positive and significant effect on financial management behavior and consumptive behavior cannot moderate the variables of financial knowledge and digital payment on financial management behavior